Comparative activity of (S)-1-(3-hydroxy-2-phosphonylmethoxypropyl)cytosine and 9-(1,3-dihydroxy-2-propoxymethyl)guanine against rat cytomegalovirus infection in vitro and in vivo. - Stals, F S (1991)
Two antiviral compounds, (S)-1-(3-hydroxy-2-phosphonylmethoxypropyl)cytosine [HPMPC] and 9-(1,3-dihydroxy-2-propoxymethyl)guanine [DHPG], were evaluated for their inhibitory effects on human cytomegalovirus (HCMV) replication in human embryonal fibroblasts and on rat cytomegalovirus (RCMV) replication in rat embryonal fibroblasts. The concentrations of HPMPC or DHPG required to inhibit HCMV plaque formation by 50% were 0.1 and 0.6 micrograms/ml, respectively. For RCMV, these values were 1.1 and 25 micrograms/ml, respectively. For HCMV, the selectivity indices of HPMPC and DHPG, as determined by the ratio of the 50% inhibitory concentration for cell growth to the 50% inhibitory concentration for virus plaque formation, were 1,250 and 140, respectively, and for RCMV, they were 500 and 76, respectively. HPMPC was far more active than DHPG against RCMV infection in vivo as measured by mortality, histopathological changes, and virus titers in organs of immunocompromised RCMV-infected rats. The minimal effective dosage required to prevent mortality from RCMV infection was a single dose of HPMPC at 2 mg/kg of body weight compared with DHPG therapy twice daily at 20 mg/kg/day for 5 days. Furthermore, HPMPC was more effective than DHPG in reducing virus titers in internal organs (P less than 0.01) and in RCMV-induced histopathologic lesions. In contrast to DHPG, which did not show activity when administered 1 day before infection, HPMPC was effective even when administered 7 days before RCMV infection.